MBER power allocation for joint precoding and space-time coding GFDM - Jianhui CAI; Guangqiu LI; Yanxu DUAN (Dianxin kexue)
In order to improve the bit error rate (BER) and bandwidth utilization performance of generalized frequency division multiplexing (GFDM) system over frequency selective fading channels, based on the minimum bit error rate (MBER) criterion, a joint precoding and space-time coding (STC) GFDM system and its corresponding power allocation strategy were proposed.The optimization goal of the power allocation strategy for the precoding STC-GFDM system can be converted from MBER to minimizing its noise enhancement factor, and the analytical expressions of its power allocation, bit error rate (BER) and bandwidth utilization were derived.Numerical calculation and simulation results show that compared with the precoding STC-GFDM system, the BER performance of precoding STC-GFDM system based on MBER criterion can be improved by about 0.4 dB when BER is 10-3, and the bandwidth utilization performance can be improved by about 0.24 bit/(s·Hz) when signal to noise ratiois 12 dB.